Effect of moderate hyperbilirubinemia on an infant’s brain: a quantitative susceptibility mapping and 1H-MRS study - Zhao, Ru; Xu, Jia-Jia; Su, Lian-Zi; Shan, Yan-Qi; Zhan, Hao; Pei, Qun; Wang, Long-Sheng; Zou, Li-Wei (Frontiers in Pediatrics, 2025)
ObjectiveThe effects of moderate neonatal hyperbilirubinemia (NHB) remain unknown. The aim of this work was to investigate whether moderate NHB has an impact on an infant’s brain and explore the relationship between brain magnetic susceptibility, brain metabolites, and biochemical tests in moderate NHB using quantitative susceptibility mapping (QSM) and magnetic resonance spectroscopy (MRS).Materials and methodsIn total, 28 term babies with moderate levels of blood bilirubin were enrolled in the NHB group, and 16 term infants were enrolled in the control group. All the patients underwent biochemical tests, 1H-MRS, and QSM examinations. Biochemical test results [e.g., direct bilirubin (DBiL)], metabolite ratios [e.g., glycerophosphocholine (GPC)], and susceptibility values were collected. The Mann–Whitney U-test was used to assess the differences between the NHB and control groups. Partial least square correlation (PLSC) analyses were performed to analyze the correlations between the biochemical results and the metabolite ratios and susceptibility values.ResultsThe Mann–Whitney U-test showed that significant differences were observed in the biochemical results, susceptibility values of the left putamen, and absolute concentrations of GPC between the NHB group and the controls. No significant differences were found in the metabolite ratios between the two groups. The PLSC analysis demonstrated that the ratios of myo-inositol (Ins), N-acetylaspartate (NAA), and GPC relative to creatine and phosphocreatine had a robust correlation with DBiL in the NHB group. Furthermore, increasing susceptibility values of putamen, globus pallidus, caudate nucleus, and thalamus had a moderate correlation with decreasing DBiL and increasing TSH concentrations in the NHB group.ConclusionThis study demonstrated that moderate hyperbilirubinemia could induce metabolic and susceptibility changes in an infant’s brain (e.g., decreased susceptibility values and metabolite values) and these changes have a correlation with biochemical test results.